Effect of aging on the quality of breast meat from broilers affected by wooden breast myopathy - de Oliveira, Rodrigo Fortunato [UNESP] (2021)
This study aimed to evaluate the effects of aging on the quality of breast meat from broilers affected of wooden breast. Samples that were classified as normal (control), moderate (hardness verified only in one region of breast fillet), and severe (hardness verified in all the extension of breast fillet) were evaluated fresh and after three and seven days of aging. Normal samples and samples with a moderate degree of myopathy showed greater water-holding capacity, which may benefit the processing industry of poultry meat. During the aging process, increase was observed in total collagen concentration (from 0.41% in normal samples to 0.56% in samples with severe degree). Samples of chicken breast affected by moderate degree showed higher myofibril fragmentation index (MFI = 115) than normal chicken samples (95.65). Although chicken samples affected with severe degree of wooden breast myopathy are more tender than normal chicken breasts, they produce more exudate, which can be detrimental to the processing of poultry meat. The aging process may improve the reduction of cooking weight loss and protein loss in exudation of broilers’ breasts affected by wooden breast myopathy.